Studying the application of officiousness in the Letting contracts - H. Naseri Moghaddam; M. Ghabooli Dorafshan; S. Mahmoudabadi (مطالعات فقه و حقوق اسلامی, 2012)
Although, there is no single definition of Letting contracts (like: borrowed, trust, Subrogation) and some have denied its very existence, but if we accept these contracts and present this minimum definition for it as " the contracts in whose nature the letting is sufficient" then we must ask that whether interference happens in them or not. There are two views about it. Some believe that interference does not happen in them because when there is the letting then there is interference or lack of interference makes no difference. While, others believe that interference in letting contracts is not problematic. The authors have strengthened the speech of probability by their reasons.